Glutathione in semen extender modulates post thaw semen quality profiles, and antioxidant and oxidative stress profiles in mithun - PERUMAL, P; VIKRAM, R; KHATE, K; VUPRU, K; SADDAMHUSEN, M N; KHAN, M H (The Indian Journal of Animal Sciences, 2022)
Present study was designed to assess the effect of glutathione (GSH) on post thaw semen quality parameters (SQPs), sperm kinetic profiles, antioxidant and oxidative stress profiles and sperm cholesterol efflux in mithun. Ejaculates (25) were selected based on biophysical parameters for the present experiment. Each sample was split into four equal aliquots after dilution with the Tris-citrate-glycerol (TCG) extender, viz. Group I (control), Group II, III and IV contained 5, 10 and 15 mM of GSH, respectively. Cryopreserved and thawed samples were analysed for their motility parameters (progressive forward and in bovine cervical mucus penetration test [BCMPT]), kinetic and velocity parameters by computer assisted sperm analyser (CASA), viability, sperm and nuclear abnormalities, acrosomal integrity, plasma membrane and nuclear integrities, sperm enzymatic leakage and biochemical (sperm cholesterol and antioxidant and oxidative stress) profiles. Study revealed a significant enhancement in viability, sperm and nuclear normalities, acrosomal integrity, motility (progressive and in cervical mucus), sperm cholesterol content and reduction in leakage of intracellular enzymes in Group III. Moreover, intactness of acrosome and biochemical membranes were protected significantly in addition to significant improvement in kinetic and velocity profiles in extender containing 10 mM GSH. These results clearly indicate that though the cryopreservation of mithun’s spermatozoa in TCG was comparable with other species, inclusion of 10 mM GSH holds a clear advantage over control and 5 or 15 mM GSH. The study concludes that GSH supplementation in semen extender can be effectively utilized to reduce the oxidative stress and improve the antioxidant profiles with cascading beneficial effects on cryopreserved semen quality parameters in mithun bull.